Combinatorics : an introduction - Faticoni, Theodore G. (John Wiley & Sons, 2013)
"This book provides a treatment of counting combinatorics and contains topical discussions beyond what is typically seen in other related books. Formulas are discussed and justified, and examples include unique approaches and ideas to the discussed topics"--